Brucellosis: The Current Situation in Iran and Neighboring Countries - Sohrabi, Amir; Hajia, Masoud (Infectious Disorders - Drug Targets, 2020)
It is frequently discussed that Brucella spp is an endemic infection in Iran and the Middle Eastern countries. The average incidence of brucellosis rate has been increasing and the zoonotic infections like brucellosis are being easily transmitted in these lands through the trafficking of livestock and chattels. A survey has been conducted to evaluate the pitfalls surrounding the diagnostic and clinical exposures of brucellosis in developing and undeveloped countries.
Keywords: Asia